2022
DOI: 10.1002/hsr2.733
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to accessing health care among young people in 30 low‐middle income countries

Abstract: Background: Previous studies focusing on high-income countries have shown that young people often face greater barriers to accessing healthcare than older adults.However, in low-middle income countries (LMICs), there have been a paucity of cross-country, quantitative studies highlighting these barriers.Aim: This exploratory study aims to provide a scoping review of the publicly available Demographic and Heath Survey (DHS) data with a view to form the basis for further work.Materials and methods: Data on insura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…Therefore, it is difficult to compare our quantitative findings related to the prevalence of selfperceived barriers to access healthcare with literature reports. Nevertheless, our findings related to socio-demographic correlates of self-reported barriers to access healthcare services are generally compatible with previous reports from the international literature [7,8,[10][11][12][13]16,[24][25][26]28].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Therefore, it is difficult to compare our quantitative findings related to the prevalence of selfperceived barriers to access healthcare with literature reports. Nevertheless, our findings related to socio-demographic correlates of self-reported barriers to access healthcare services are generally compatible with previous reports from the international literature [7,8,[10][11][12][13]16,[24][25][26]28].…”
Section: Discussionsupporting
confidence: 92%
“…A recent scoping review reported on the barriers to accessing healthcare among young people in 30 low-middle income countries [25]. Overall, significantly greater barriers to accessing healthcare were reported in the younger populations compared to older adults [25]. Therefore, the available evidence suggests that young people often face additional barriers to accessing healthcare in many low-middle income countries, which resembles findings across many high-income countries [25].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations